Oxidation of 5-Hydroxymethylfurfural on Supported Ag, Au, Pd and Bimetallic Pd-Au Catalysts: Effect of the Support; Catalysts; Vol. 11, iss. 1 - German D. Yu. Dmitry Yuryevich; Pakrieva E. G. Ekaterina Germanovna; Kolobova E. N. Ekaterina Nikolaevna; Carabineiro S. A. C. Sonia Alexandra Correia; Stucchi M. Marta; Villa A. Alberto; Prati L. Laura; Bogdanchikova N. Nina; Cortes C. V. Corberan; Pestryakov A. N. Aleksey Nikolaevich (2021, 2021)
Title screen